Sports Activities During The Covid-19: Literature Review - Wildani, Lutfi; Gazali, Novri (Journal of Physical Education Health and Sport, 2020)
This review article was conducted to provide an overview of sports activities during the Covid-19 pandemic. The method used in this study is the method of literature study or literature review. Literature study is a series of activities related to library data collection methods, reading and recording, and managing research material. This technique is carried out with the aim of expressing various theories that are relevant to the problem being studied as reference material in the discussion of research results. In a search carried out through Boolean Operators using the keyword â€œSport and Covid-19â€ on the website produced 273 findings, then narrowed by 2020, free full text found 206 findings, then narrowed back to journal articles, human species, English language, found there are 61 findings. After that the data obtained is excluded according to the needs of researchers so that they get 5 data articles. Research results show that many large-scale sports activities must be stopped, but exercise also has a positive impact on increasing endurance or immunity so that the body can strengthen itself from viruses or bacteria.